Father Christmas goes on holiday - Briggs, Raymond (New York : Puffin Books, 1977)
Father Christmas visits France, Scotland, and Las Vegas while on his annual vacation.
Booklist.
School Library Journal.
3.0
3-6
Keywords: Cartoons and comics; Santa Claus -- Fiction; Vacations -- Fiction; Santa Claus -- Fiction